Towards Sustainable H2 Production: Rational Design of Hydrophobic Triphenylamine‐based Dyes for Sensitized Ethanol Photoreforming. Issue 4 (31st January 2018) - Dessì, Alessio; Monai, Matteo; Bessi, Matteo; Montini, Tiziano; Calamante, Massimo; Mordini, Alessandro; Reginato, Gianna; Trono, Cosimo; Fornasiero, Paolo; Zani, Lorenzo
Abstract: Donor–acceptor dyes are a well‐established class of photosensitizers, used to enhance visible‐light harvesting in solar cells and in direct photocatalytic reactions, such as H2 production by photoreforming of sacrificial electron donors (SEDs). Amines—typically triethanolamine (TEOA)—are commonly employed as SEDs in such reactions. Dye‐sensitized photoreforming of more sustainable, biomass‐derived alcohols, on the other hand, was only recently reported by using methanol as the electron donor. In this work, several rationally designed donor–acceptor dyes were used as sensitizers in H2 photocatalytic production, comparing the efficiency of TEOA and EtOH as SEDs. In particular, the effect of hydrophobic chains in the spacer and/or the donor unit of the dyes was systematically studied. The H2 production rates were higher when TEOA was used as SED, whereas the activity trends depended on the SED used. The best performance was obtained with TEOA by using a sensitizer with just one bulky hydrophobic moiety, propylenedioxythiophene, placed on the spacer unit. In the case of EtOH, the best‐performing sensitizers were the ones featuring a thiazolo[5, 4‐ d ]thiazole internal unit, needed for enhancing light harvesting, and carrying alkyl chains on both the donor part and the spacer unit. The results are discussed in terms of reaction mechanism, interaction with the SED, and structural/electrochemical properties of the sensitizers. Abstract : The sacrifice of ethanol : Photocatalytic H2 production mediated by organic dye‐sensitized Pt/TiO2 nanopowders is investigated by using triethanolamine and, for the first time, ethanol as sacrificial electron donors (SEDs). Results indicate that good compatibility between individual dye properties and the particular SED used in the experiment is vital to maximize catalytic efficiency.